Experimental Study on the Effect of Oxidation on the Compressibility of Iron Powder - Al- Saraireh, Falah Mustafa (Manufacturing Technology Journal, 2023)
An experimental study was carried out on the effect of oxidation temperature and the oxide film composition on the compressibility of porous materials. samples were annealed at different temperatures; the size change in the samples after annealing was measured. The phase composition of the oxide layer was investigated. Magnetite was generated at between 350 and 450°C, and two-phase oxide was formed at 550°C, after oxidation, weight gain was determined. The presence of pore overgrowth, which reduces porosity, was confirmed by metallographic tests. The maximum porosity is found in the oxidized samples produced by pressing at room temperature. The process of high-temperature oxidation of iron powder before pressing and in the state of free filling in a fluidized bed, as well as the effect of the content of oxides on magnetic characteristics, has been studied. The impact of oxidation on the compressibility of samples of iron powder was investigated. In this study, It was observed that the range of 350-450°C, which offers the best compressibility and the necessary composition of the oxide film, is also related to the presence of magnetite in the iron oxide coating. is the ideal temperature for oxidation and repressing. the deformation of porous materials exposed to iron powder oxidation was tested.
Keywords: Oxidation; Iron powder; Soft magnetic materials; Deformation; Porous materials